Walking in a dental environment with the “UniCDent” tool kit—part 1: a participatory tool with legs! - Eachempati, Prashanti; Martin, John; Hanks, Sally; Nasser, Mona (Frontiers in Oral Health, 2025)
This case study explores the adaptation of the walking method coupled with auto-photography and photo elicitation, a participatory research tool traditionally used in landscape studies, for application in dental research settings. By presenting the UniCDent toolkit, we demonstrate how this immersive method can enhance understanding of patient experiences in dentistry through sensory engagement and spatial exploration. The toolkit comprises four components: Imagery, Gallery Walk, Quadrant Mapping, and Trade-offs, each designed to facilitate active participation and foster in-depth reflections on the dental environment. Participants navigate a simulated dental clinic, documenting their sensory experiences and social interactions, thereby enriching the data collected. This multi-layered approach allows researchers to capture the complexities of patient experiences, providing insights that are applicable across various research projects within dentistry. The commentary highlights the versatility of the walking method, emphasising its role in improving patient-centred care by capturing patient experiences and perspectives. It also demonstrates its value in enhancing the understanding of diverse research enquiries in dental research.